Sequence of Alzheimer disease biomarker changes in cognitively normal adults: A cross-sectional study. (8th December 2020) - Luo, Jingqin; Agboola, Folasade; Grant, Elizabeth; Masters, Colin L.; Albert, Marilyn S.; Johnson, Sterling C.; McDade, Eric M.; Vöglein, Jonathan; Fagan, Anne M.; Benzinger, Tammie; Massoumzadeh, Parinaz; Hassenstab, Jason; et al.
Abstract : Objective: To determine the ordering of changes in Alzheimer disease (AD) biomarkers among cognitively normal individuals. Methods: Cross-sectional data, including CSF analytes, molecular imaging of cerebral fibrillar β-amyloid (Aβ) with PET using the [ 11 C] benzothiazole tracer Pittsburgh compound B (PiB), MRI-based brain structures, and clinical/cognitive outcomes harmonized from 8 studies, collectively involving 3, 284 cognitively normal individuals 18 to 101 years of age, were analyzed. The age at which each marker exhibited an accelerated change (called the change point) was estimated and compared across the markers. Results: Accelerated changes in CSF Aβ1-42 (Aβ42 ) occurred at 48.28 years of age and in Aβ42 /Aβ40 ratio at 46.02 years, followed by PiB mean cortical standardized uptake value ratio (SUVR) with a change point at 54.47 years. CSF total tau (Tau) and tau phosphorylated at threonine 181 (Ptau) had a change point at ≈60 years, similar to those for MRI hippocampal volume and cortical thickness. The change point for a cognitive composite occurred at 62.41 years. The change points for CSF Aβ42 and Aβ42 /Aβ40 ratio, albeit not significantly different from that for PiB SUVR, occurred significantly earlier than that for CSF Tau, Ptau, MRI markers, and the cognitive composite. Adjusted analyses confirmed that accelerated changes in CSF Tau, Ptau, MRI markers, and the cognitive composite occurred at ages not significantly different from each other. Conclusions: Our findings support the hypothesized early changes of amyloid in preclinical AD and suggest that changes in neuronal injury and neurodegeneration markers occur close in time to cognitive decline.